Considerations and recommendations for conducting qualitative research interviews with palliative and end-of-life care patients in the home setting: a consensus paper. Issue 1 (8th December 2015) - Sivell, Stephanie; Prout, Hayley; Hopewell-Kelly, Noreen; Baillie, Jessica; Byrne, Anthony; Edwards, Michelle; Harrop, Emily; Noble, Simon; Sampson, Catherine; Nelson, Annmarie
Abstract : Objectives: To present and discuss the views of researchers at an academic palliative care research centre on research encounters with terminally ill patients in the home setting and to generate a list of recommendations for qualitative researchers working in palliative and end-of-life care. Methods: Eight researchers took part in a consensus meeting to discuss their experiences of undertaking qualitative interviews. The researchers were of varying backgrounds and all reported having experience in interviewing terminally ill patients, and all but one had experience of interviewing patients in their home environment. Results: The main areas discussed by researchers included: whether participation in end-of-life research unintentionally becomes a therapeutic experience or an ethical concern; power relationships between terminally ill patients and researchers; researcher reflexivity and reciprocity; researchers' training needs. Qualitative methods can complement the home environment; however, it can raise ethical and practical challenges, which can be more acute in the case of research undertaken with palliative and patients at the end-of-life. Conclusions: The ethical and practical challenges researchers face in this context has the potential to place both participant and researcher at risk for their physical and psychological well-being. We present a set of recommendations for researchers to consider prior to embarking on qualitative research in this context and advocate researchers in this field carefully consider the issues presented on a study-by-study basis.